Activating PTEN Tumor Suppressor Expression with the CRISPR/dCas9 System - Colette Moses; Fiona Nugent; Charlene Babra Waryah; Benjamin Garcia-Bloj; Alan R. Harvey; Pilar Blancafort (Elsevier, 2019)
PTEN expression is lost in many cancers, and even small changes in PTEN activity affect susceptibility and prognosis in a range of highly aggressive malignancies, such as melanoma and triple-negative breast cancer (TNBC). Loss of PTEN expression occurs via multiple mechanisms, including mutation, transcriptional repression and epigenetic silencing. Transcriptional repression of PTEN contributes to resistance to inhibitors used in the clinic, such as B-Raf inhibitors in BRAF mutant melanoma. We aimed to activate PTEN expression using the CRISPR system, specifically dead (d) Cas9 fused to the transactivator VP64-p65-Rta (VPR). dCas9-VPR was directed to the PTEN proximal promoter by single-guide RNAs (sgRNAs), in cancer cells that exhibited low levels of PTEN expression. The dCas9-VPR system increased PTEN expression in melanoma and TNBC cell lines, without transcriptional regulation at predicted off-target sgRNA binding sites. PTEN activation significantly repressed downstream oncogenic pathways, including AKT, mTOR, and MAPK signaling. BRAF V600E mutant melanoma cells transduced with dCas9-VPR displayed reduced migration, as well as diminished colony formation in the presence of B-Raf inhibitors, PI3K/mTOR inhibitors, and with combined PI3K/mTOR and B-Raf inhibition. CRISPR-mediated targeted activation of PTEN may provide an alternative therapeutic approach for highly aggressive cancers that are refractory to current treatments. Keywords: human PTEN protein, CRISPR/Cas systems, tumor suppressor genes, melanoma, breast neoplasms